Amid political recalibrations: Strike wave hits Ethiopia. (27th August 2018) - Admasie, Samuel Andreas
Abstract : While the political protests that have gripped Ethiopia in recent years and the recalibrations within the ruling front that they have generated have been the subject of extensive attention, another aspect of ongoing social turbulence has been almost entirely neglected: the wave of labor unrest apparent since the autumn of 2017. No less than a dozen strikes have been recorded, in addition to a number of other signs of growing restiveness among wage workers. This commentary seeks to shed light on the ongoing strike wave and the social conditions that underpin it. They include real wages that have dropped to a historical record low, and are reinforced by attempts to further erode labor rights.